К распространению гвоздичниковых (Cestoda, Caryophyllideidae) - Кулаковская, О.П. (Вестник зоологии, 1967)
At present time 80 species of Caryophyllaeidae are known in world fauna. The greatest number of them (36 species) are registrated in tropical countries, pertaining to Indomalyan, Ethiopian and Australian zoogeographical zones. 22 species are known in the Palearctic, 22 species in the Neoarctic. In the reservoirs of the Soviet Union 21 species of the Caryophyllaeidae were found among which some groups can be distinguished: 1) European group (11 species); 2) sinoindian group (2 species); 3) the Amur endemics (3 species); 4) species of vague origin: a -- with interrupted areal (3 species) and b — with narrow (endemics) areal (2 species). Pont-Aral-Caspian province and the Amur area are the main zones of spreading of Caryophyllaeidae in the Soviet Union, sometimes this species can be found in Siberian area of Circumpolar subregion.